NATIONAL INNOVATIVE DOCTRINE: DRAFT PROPOSALS - M. I. Demchuk; A. T. Urkevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers some problems relevant to formation of National innovative doctrine. The proposals concerning creation of new scientifically-based fields of energy consumption and alternative energy supply of the economy of the Republic of Belarus have been given in the paper.